1993
DOI: 10.1111/j.1600-0447.1993.tb03359.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal perception of body weight is not solely observed in pubertal girls: incorrect body image in children and its relationship to body weight

Abstract: Perceived actual body weight and perceived ideal weight were assessed in 255 Japanese children and adolescents (130 boys, 125 girls) aged 6 years through 18 years using the drawing test to clarify whether they wanted to be thinner or to gain weight. More than half (68%) of the girls attending high school and 41% of the elementary school girls perceived their ideal weight to be less than the standard. The mean difference between the perceived actual weight and the ideal weight was positive in the high school gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…It is demonstrated that fear of obesi ty may be found before puberty as well as in adolescent girls. The results are consistent with the proposal that weight phobia is not always necessary for a diagnosis of anorexia nervosa and rather related with culture [8] and also with the previous studies [17,18] that the desire for thinness was found in girls without anorexia nervosa. Eating behavior and its derangement in prepubertal girls seem similar, but not identical, to those in adoles cents.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It is demonstrated that fear of obesi ty may be found before puberty as well as in adolescent girls. The results are consistent with the proposal that weight phobia is not always necessary for a diagnosis of anorexia nervosa and rather related with culture [8] and also with the previous studies [17,18] that the desire for thinness was found in girls without anorexia nervosa. Eating behavior and its derangement in prepubertal girls seem similar, but not identical, to those in adoles cents.…”
Section: Discussionsupporting
confidence: 81%
“…How ever, distorted body image does not seem the sole cause of eating disorder because the dis tortion is also found in many normal-weight girls without anorexia nervosa [4,12,13,[16][17][18], In addition, cases of nonweight-phobic anorexia nervosa were demonstrated [8], It is proposed that other factors, such as maturational conflict or changes in hormonal secre tion which occur in the pubertal period, prob ably contribute to the onset of eating disor ders in adolescent girls [24,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the authors noted that both the test-retest and internal reliability measures for the scale were high. Over the past 6 years, several other researchers have published findings that indicate a similar trend in preadolescents' development of perceived body-image dissatisfaction and restrictive dietary behaviors (Ohtahara, Ohzeki, Hanaki, Motozumi, & Shiraki, 1992; Rhyne-Winkler, 1994; Rolland et al, 1997;Thelen et al, 1992). For example, a study by Thelen et al (1992) of eating and bodyimage concerns among 19 1 non-obese children (74 in second grade, mean age 8.2 years; 54 in fourth grade, mean age 10.4 years; 63 in sixth M e , mean age 12.4 years) indicated that young girls begin to be concerned about weight between second and fourth grades, concurring with the proposal by Maloney et al (1989) that the genesis is around Grade 3.…”
mentioning
confidence: 91%
“…In recent years, a number of studies in Japan have established normative levels of eating psychopathology and of related morbidity (Furukawa, 1994;Kiriike, Nagata, Tanaka, Matsunaga, 1988;Kuboki, Nomura, Kumano, & Suematsu, 1996;Matsunaga & Kiriike, 1997). Other Japanese researchers have begun to explore the psychological and dietary factors that might underpin eating problems in their culture (Matsumoto, Kumano, & Sakano, 1997;Ohtahara, Ohzeki, Hanaki, Motozumi, & Shiraki, 1993;Ono et al, 1996). Finally, there is considerable interest in the Japanese literature in the issue of treatment (Kikuchi, 1996;Naruo, Homan, Soejima, Nozoe, & Tanaka, 1996;Taguchi, Kawakami, & Yamauchi, 1996).…”
Section: Introductionmentioning
confidence: 97%